The Building Blocks of Child Bilingual Code-Mixing: A Cross-Corpus Traceback Approach - Quick, Antje Endesfelder; Hartmann, Stefan (Frontiers in Psychology, 2021)
This paper offers an inductive, explorative study on the role of input and individual differences in the early code-mixing of bilingual children. Drawing on data from two German-English bilingual children, aged 2 to 4, we use the so-called traceback method to check whether their code-mixed utterances can be accounted for with the help of constructional patterns that can be found in their monolingual data and/or in their caregivers’ input. In addition, we apply the traceback method to check whether the patterns used by one child can also be found in the input of the other child. Results show that patterns found in the code-mixed utterances could be traced back to the input the children receive suggesting that children extract lexical knowledge from their environment. Additionally, tracing back patterns within each child was more successful than to the other child’s corpus, indicating that each child has their own set of patterns which depends very much on their individual input. As such, these findings can shed new light on the interplay of the two developing grammars in bilingual children and their individual differences.